2007
DOI: 10.1152/ajpheart.01148.2006
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular plane displacement is the major contributor to left ventricular pumping in healthy adults, athletes, and patients with dilated cardiomyopathy

Abstract: Previous studies using echocardiography in healthy subjects have reported conflicting data regarding the percentage of the stroke volume (SV) of the left ventricle (LV) resulting from longitudinal and radial function, respectively. Therefore, the aim was to quantify the percentage of SV explained by longitudinal atrioventricular plane displacement (AVPD) in controls, athletes, and patients with decreased LV function due to dilated cardiomyopathy (DCM). Twelve healthy subjects, 12 elite triathletes, and 12 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
229
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(242 citation statements)
references
References 42 publications
8
229
1
4
Order By: Relevance
“…The relation between aortic stiffness and diastolic function is often attributed to hemodynamic effects, while the relation between GLS and diastolic function has been attributed to recoil of contracted LV muscle fibers 49, 50. Recent studies have suggested that diastolic recoil of the aorta and left atrium, which are stretched during systole, facilitates LV filling and ejection 12, 51, 52, 53, 54, 55. The association between increased aortic stiffness and worse GLS observed in our study may relate to both the systolic and diastolic components of direct mechanical ventricular–vascular coupling and requires further study 48…”
Section: Discussionmentioning
confidence: 99%
“…The relation between aortic stiffness and diastolic function is often attributed to hemodynamic effects, while the relation between GLS and diastolic function has been attributed to recoil of contracted LV muscle fibers 49, 50. Recent studies have suggested that diastolic recoil of the aorta and left atrium, which are stretched during systole, facilitates LV filling and ejection 12, 51, 52, 53, 54, 55. The association between increased aortic stiffness and worse GLS observed in our study may relate to both the systolic and diastolic components of direct mechanical ventricular–vascular coupling and requires further study 48…”
Section: Discussionmentioning
confidence: 99%
“…We studied 12 healthy volunteers, 12 Swedish national elite triathletes, and 12 patients with dilated cardiomyopathy (ejection fraction Ͻ30%). We have studied this population previously (6).…”
Section: Methodsmentioning
confidence: 99%
“…All subjects underwent CMR imaging in the supine position. Imaging was undertaken with a 1.5T scanner (Intera; Philips, Best, The Netherlands) using a five-element cardiac synergy coil and a cine steady-state free precession sequence as previously described (6). Cine image acquisition included a contiguous short-axis stack and also the two-chamber, four-chamber, and left ventricular outflow tract long-axis views.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(10) The mechanism for TID appears to be multifactorial, with sub endocardial ischemia temporary systolic dysfunction (11) and a true increase in the size of the left ventricle having been proposed as explanations for the phenomenon. (12,13) MAPSE has been proposed as a well-established clinically useful echocardiographic parameter for the assessment of LV longitudinal function and correlates with global systolic function of the LV (14,15) . Previous clinical studies showed that, MAPSE, which reflects the mitral ring displacement at systole, can be used to assess cardiac global longitudinal function and is a sensitive parameter to define slight abnormalities in various patients with cardiovascular diseases at early stage where longitudinal function is affected before other components (which can even be increased in compensation).…”
Section: Introductionmentioning
confidence: 99%